2020
DOI: 10.1039/d0cp02750b
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of alkali-metals on the B12 skeleton

Abstract: After an exhaustive exploration of the potential energy surface of B12E- and B12E2 (E=Li-Cs) systems, it was found that, for the anionic series, a cage-type and a quasi-planar structure, very...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…We compute the T 1 diagnostic to determine if the energy evaluation scheme is properly described by a single reference method of the Be 4 B 8 cluster or contains a multireference character. Our results confirm that the computed T 1 diagnostic values are below the recommended threshold of 0.02 [ 122 , 129 ] for all low-energy isomers. Hernandez et al [ 122 ] found similar values for the T 1 descriptor in doped boron clusters.…”
Section: Theoretical Methods and Computational Detailssupporting
confidence: 80%
See 1 more Smart Citation
“…We compute the T 1 diagnostic to determine if the energy evaluation scheme is properly described by a single reference method of the Be 4 B 8 cluster or contains a multireference character. Our results confirm that the computed T 1 diagnostic values are below the recommended threshold of 0.02 [ 122 , 129 ] for all low-energy isomers. Hernandez et al [ 122 ] found similar values for the T 1 descriptor in doped boron clusters.…”
Section: Theoretical Methods and Computational Detailssupporting
confidence: 80%
“…Our multi-step strategy employs more accurate levels of theory applied to each step to arrive at the most stable lowest-lying isomers. In the first step of our methodology, the code builds an initial random population of 3D structures (two hundred structures per atom of the Be 4 B 8 cluster), employing a strategy used in previous works [ 21 , 33 , 113 , 116 , 117 , 118 , 121 , 122 , 123 ]. The first optimization was carried out at the PBE0 [ 124 ]/LANL2DZ [ 125 ] level.…”
Section: Theoretical Methods and Computational Detailsmentioning
confidence: 99%
“…A large number of studies have shown that metal modification can effectively compensate for the electron deficiency of boron and change the structures and properties of boron clusters [16‐33]. Joint photoelectron spectroscopy (PES) and first‐principles theory (FPT) investigations have shown that M©B n − (M = Co, Rh, Ir, Ru, Ta, Nb, n = 8–10) possess two dimensional (2D) wheels [16‐18].…”
Section: Introductionmentioning
confidence: 99%
“…Not only the type of the metals, the number of them also have significant influence on the structures of boron clusters [29‐33]. Two low‐lying isomers of binary Be 6 B 11 − : the coaxial triple‐layered cluster with structural fluxionality and helical cluster with multifold aromaticity, are anticipated to be co‐existence in the gas‐phase experiments [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation